Analysis on the relationship between coastal tourism and marine pollution: an empirical analysis of China’s 11 coastal regions - Ji, Xina; Ding, Xingong (Frontiers in Marine Science, 2024)
Introduction Coastal tourism has become an important pillar of economic growth in China's coastal regions, yet no quantitative research has analyzed the relationship between coastal tourism and marine pollution. Methods This study, within a multivariate framework, comprehensively examines the impact of coastal tourism on marine pollution by employing various econometric techniques and focusing on four different types of marine pollutant discharges: chemical oxygen demand (COD), petroleum (PET), ammonia nitrogen (NHN), and total phosphorus (TP). Results and discussion Panel cointegration tests confirm a long-term relationship between coastal tourism and these four types of marine pollutant discharges. In the long run, coastal tourism has a significantly negative impact on COD, NHN, and TP. The results of Pooled Mean Group (PMG), Fully Modified Ordinary Least Squares (FMOLS), and Dynamic Ordinary Least Squares (DOLS) estimators show that for every 1% increase in coastal tourism revenue (TOUR), COD decreases by 0.734%, 0.536%, and 0.952% respectively; NHN decreases by 0.746%, 0.340%, and 1.633%; and TP decreases by 5.169%, 0.899%, and 0.334% respectively. However, the impact of coastal tourism on PET is not significant. The Dumitrescu-Hurlin (D-H) panel causality test results indicate different causality patterns between coastal tourism and various marine pollutant discharges. Specifically, there is a bidirectional causality between coastal tourism and COD, NHN, and a unidirectional causality between coastal tourism and PET, TP. Moreover, heterogeneity analysis reveals that coastal tourism does not significantly reduce all marine pollutant discharges in low-and middle-income coastal regions. Furthermore, compared to the central and southern coastal regions, the coastal tourism of northern regions has not significantly reduced marine pollution. This study can provide policymakers with references for developing coastal tourism and reducing marine pollutant discharges.